PERILAKU PENGGUNA RUANG PUBLIK DI KOMPLEKS MILITER BATALYON ARTILERI MEDAN 10 BOGOR - Listya Aderina; Ray March Syahadat; Priambudi Trie Putra (Unika Soegijapranata Semarang, 2018)
The military settlement (ksatrian), is an area where soldiers live with their families. Arrangements within military settlement generally feature a firm, rigid, static and monotonous to maintain private boundaries. But often the boundaries become unclear because in the public areas are also found the same ambiance. Not optimal use of public space due to the citizens' resentment becomes the trigger of the problem. To re-optimize the role of public space in the life of the citizens of ksatrian, an analysis is needed to perform a rearrangement based on the needs of the user, physical facilities, thermal comfort and visual aesthetic. This research through 3 (three) stages that is location observation, behavior setting analysis with person-centered mapping approach and recommendation in 4 (four) location observation. Prominent activities found in all public spaces are cycling, chatting, running, feeding children, playing kites, playing jump rope, soccer, and basketball. In each observation area found activity that is not in accordance with the function of the space. The mismatched landscape usage is caused by the non-fulfillment of recreational facilities that the residents need. Proper landscape element arrangement can result in good interaction between users and the landscape as a basis for improving the quality of the battalion